2022
DOI: 10.5194/essd-14-2147-2022
|View full text |Cite
|
Sign up to set email alerts
|

Integrated hydrogeological and hydrogeochemical dataset of an alpine catchment in the northern Qinghai–Tibet Plateau

Abstract: Abstract. Climate warming has significantly changed the hydrological cycle in cold regions, especially in areas with permafrost or seasonal frost. Groundwater flow and its interactions with surface water are essential components of the hydrological process. However, few studies or modeling works have been based on long-term field observations of groundwater level, temperature, hydrogeochemistry, or isotopic tracers from boreholes due to obstacles such as remote locations, limited infrastructure, and harsh work… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…The influencing factors of conductivity are rainfall amount, rainfall duration, soil moisture before rainfall, and runoff depth (Figure 5). This is consistent with the results of some previous studies (Meriano et al, 2011;Pan et al, 2018). The number of rainfall events and rainfall are less at the beginning of the sampling period, which is conducive to the infiltration of rainfall (Hoeg et al, 2000;Carey and Quinton, 2005;Mueller et al, 2016), so the conductivity shows an increasing trend.…”
Section: Influencing Factors Of Stream Water Isotope and Conductivitysupporting
confidence: 92%
See 1 more Smart Citation
“…The influencing factors of conductivity are rainfall amount, rainfall duration, soil moisture before rainfall, and runoff depth (Figure 5). This is consistent with the results of some previous studies (Meriano et al, 2011;Pan et al, 2018). The number of rainfall events and rainfall are less at the beginning of the sampling period, which is conducive to the infiltration of rainfall (Hoeg et al, 2000;Carey and Quinton, 2005;Mueller et al, 2016), so the conductivity shows an increasing trend.…”
Section: Influencing Factors Of Stream Water Isotope and Conductivitysupporting
confidence: 92%
“…Comparing Event I and Event II, it can be found that although the rainfall and rainfall duration of the two rainfall events are similar, the runoff depth and runoff composition (whether by IHS or CMB method) are significantly different. The soil moisture condition before the rainfall event is the root cause of this difference (Penna et al, 2011;Pan et al, 2018). Before the occurrence of Event I, the soil was in a relatively dry state.…”
Section: Hydrograph Separationmentioning
confidence: 99%
“…The results of the endmember calculation from April 2015 to September 2016 also indicate the dominance of the groundwater in the seasonally frozen area to DOC flux at the catchment outlet, which could reach as high as 90% (Figure 9). We assumed that this conclusion also applied in other hydrological years since the hydrological conditions between the years were generally consistent from 2013 to 2019 as show by the similarly seasonal variations of temperature, precipitation, stream discharge and groundwater level in the study area (Ma et al, 2017(Ma et al, , 2021Pan et al, 2022). According to the differences in the DOM chemical features between the groundwater and stream water (Figures 7 and 8), it is clear that the dominant contribution of groundwater DOC to the total DOC flux increased the proportion of protein-like DOM with low aromaticity in the main stream water.…”
Section: Hydrological Control On Seasonality In Doc Concentration And...mentioning
confidence: 72%
“…The monitored temperature data in the study area indicated that the active layer in the permafrost area and shallow soil in the seasonally frozen area are completely frozen from late November to March (defined as frozen period), start to thaw from April to May (thawing period), are completely thawed from June to early October (thawed period), and refreeze back from late October to November (refreezing period) (Figure S1 in Supporting Information ; Ma et al., 2021; Pan et al., 2022).…”
Section: Study Areamentioning
confidence: 99%